PEMANFAATAN PENINGGALAN SEJARAH KRATON SURAKARTA SEBAGAI MATERI PENGEMBANGAN MATA PELAJARAN IPS SEKOLAH DASAR (Studi Kasus di Sekolah Dasar Negeri Kecamatan Banjarsari Surakarta) - Sarafuddin, Sarafuddin (UNIVERSITAS SLAMET RIYADI, 2016)
This study aims to determine: (1) The content / material taught social studies at theState Elementary School District of Banjarsari; (2) the way teachers develop the content /materials in social studies at State Elementary School District of Banjarsari, and (3) The valuespaedagogis of Kraton Surakarta historical heritage which can be used as material developmentof social studies at the State Elementary School District of Banjarsari.This research was conducted at the State Elementary School District of Banjarsari andin Kasunanan, Mangkunegaran and Museum Radyapustoko. Form of research is descriptivequalitative single case study strategy spikes. Source of data derived from informants, places andevents as well as documents. Data collection was carried depth interviews with teachers,principals, and employees Kasunanan, Mangkunegaran and Museum Radyapustoko and otherinformants who really know the historical heritage Kraton Surakarta. Observations carried outon learning activities in the classroom social studies, Kasunanan, Mangkunegaran and MuseumRadyapustoko. Analysis of documents related to historical relics and documents KratonSurakarta curriculum and learning tools, especially social studies teacher. Sampling ispurposive sampling, time sampling and sampling snowbal. To obtain the validity of data usedtriangulation data / sources and methods. The data analysis technique used is interactiveanalysis, the analysis process that moves between the three components include data reduction,data presentation and verification / drawing conclusions that interact with the data collectioncycle.The conclusion of this study: (1) The content / material elementary school social studiesis still a general knowledge about the development of Hindu-Buddhist kingdom and the kingdomof Islam, so the historical heritage Kraton Surakarta not been included as study material; (2) Indeveloping the content / learning material social studies, teachers still use other sources, whilethe historical heritage Kraton Surakarta not be the object of the assignment, and (3) Historicalevidence Kraton Surakarta has left some value paedagogis both from a religious / religious,politically, economically, and culturally so worthy to serve as the development of social studiesmaterials can even be used as study material.Keywords: The historical heritage, development of learning materials, subjects IPS.